Architectural influence of a large room on thermal comfort numerical Analysis - LACRI AYMEN; BOUAZARA ABDELDJALIL; AMINE TOUFIK BENHOUIA (AMAR THELIDJI UNIVERSITY – LAGHOUAT -FACULTY OF TECHNOLOGY DEPARTMENT OF MECHANICAL ENGINEERING, 2025)
This study investigated the architectural influence of large rooms, specifically mosque prayer halls, on thermal comfort using computational fluid dynamics (CFD) simulations. Simulations of various mosque configurations, including those with open doors and windows at different distances and heights, revealed significant impacts on indoor thermal conditions. The findings provide insights into effective design strategies for enhancing thermal comfort in mosque environments during both summer and winter, contributing to the development of more sustainable and comfortable worship spaces.
OPTION: ENERGETIC